Learning Motivation and its Relationship With Writing Achievement at the State Senior High School 8 Jambi City - Mira Ermita; Halimah (MultiTech Publisher, 2025)
This study examines the relationship between learning motivation and students' English writing achievement. This study uses a descriptive method with correlational analysis. The respondents of the study were grade X students at The State Senior High School 8 Jambi City in the 2024/2025 Academic Year. The sampling technique was a random technique, obtaining 34 students. Data collection was carried out by distributing questionnaires to determine students' English learning motivation and writing tests were conducted to determine students' writing achievement. The type of writing test given is a descriptive type. Meanwhile, to measure the correlation of research data, the researcher used Pearson-Product Moment with calculations using SPSS 25. The results of the study showed a strong relationship between motivation and students' writing achievement.